PENGARUH STATUS SOSIAL EKONOMI DAN LINGKUNGAN KAMPUS TERHADAP IPK MAHASISWA - Rohiyah, Siti; Handayani, Femi; Widiarti, Aniek (Journal of Business Education and Social, 2022)
The Grade Point Average (GPA) is a measurement and assessment of learning outcomes that have been carried out by someone after carrying out learning activities as evidenced by the form of tests and learning outcomes expressed in the form of numbers and letters that have been achieved. This study aims to determine how much influence socio-economic status and campus environment have on student GPA at the Faculty of Teaching and Education, Syekh-Yusuf Islamic University Tangerang. The author uses a representative sample of students who are registered and active in the Teaching and Education Faculty of the Syekh-Yusuf Tangerang Islamic University, totaling 56 samples. Data obtained with valid and reliable research instruments. The author uses a Likert scale as a measurement scale and distributes a predetermined questionnaire with simple random sampling. With multiple regression analysis, the authors found that socio-economic status had a significant effect on the cumulative grade point average of students while the campus environment was not significant.